2012
DOI: 10.1175/jamc-d-11-012.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial and Boundary Conditions of Mesoscale Models on Simulated Atmospheric Refractivity

Abstract: Radar ducting is caused by sharp vertical changes in temperature and, especially, water vapor at the top of the atmospheric boundary layer, both of which are sensitive to variations in the underlying surface conditions, local mesoscale weather, and synoptic weather patterns. High-resolution numerical weather prediction (NWP) models offer an alternative to observation to determine boundary layer (BL) structure and to assess the spatial variability of radar ducts. The benefit of using NWP models for simulating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Wang et al . [] also reported that an enhanced SB can result in more numerous surface ducts. At an altitude of 100–400 m agl (Figures c and b), a region of subrefractive conditions (~70 km offshore from the western Istrian coast) formed because of the drier layer at the top of the lower branch of the SB cell.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Wang et al . [] also reported that an enhanced SB can result in more numerous surface ducts. At an altitude of 100–400 m agl (Figures c and b), a region of subrefractive conditions (~70 km offshore from the western Istrian coast) formed because of the drier layer at the top of the lower branch of the SB cell.…”
Section: Resultsmentioning
confidence: 71%
“…Considering the relatively low sampling frequency (usually every 6 or 12 h) and the infrequent and irregular spatial distribution of radio sounding measurements, improvements can be achieved be employing a mesoscale model with a high resolution (both vertically and horizontally). Such studies [e.g., Burk et al ., ; Atkinson and Zhu , , ; Bech et al ., ; Haack et al ., ; Thompson and Haack , ; Wang et al ., ; Karimian et al ., ] are relatively recent, having been conducted within the last decade, because they are highly dependent on the development of atmospheric models and the increase in available computer capacity. On the California coast, based on extensive research (radio sounding and aircraft measurements) in combination with a numerical model, Haack and Burk [] related the structure and depth of the marine ABL, finding variations in trapping primarily at the top of the ABL, where the gradients in humidity and temperature were the most pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, we used gravity wave drag as a momentum-damping mechanism. The model vertical atmospheric structure strongly depends on the initialization of surface fields and model spin-up time (Wang et al, 2012). As mesoscale convective systems evolve due to specific vertical atmospheric structure, we performed sensitivity analysis of the spin-up time to properly calibrate the model.…”
Section: Model Description and Experiments Setupmentioning
confidence: 99%
“…Some of these variables can be used to diagnose the spatiotemporal variation of atmospheric refractivity for simulating or forecasting optical phenomena such as optical ducting and mirage formation. This technique has been adopted in a handful of research studies to document the influences of heterogeneous refractivity on propagation of radio wave (Burk and Thompson 1997;Atkinson et al 2001;Haack et al 2010;Wang et al 2012). In our recent work , a coupled mesoscale modeling and ray tracing framework was utilized to investigate the impacts of anomalous refractivity, induced by the periodic shedding of island wake vortices, on long-range optical wave propagations.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these uncertainties may be high and often times sensitive to the particular flow being simulated (Wang et al 2012). This paper concentrates on modeling of optical ray trajectories originating, and traveling through, the planetary boundary layer (PBL).…”
Section: Introductionmentioning
confidence: 99%